A Phenomenological Analysis of the Spiritual Support Services in State Hospitals: The Case of Turkey - BAKİLER, ESRA; EKŞİ, HALİL (SAGE PUBLICATIONS INC, 2018)
The purpose of this research is to examine the core and nature of spiritual support services experienced by Turkey's pioneer spiritual support specialists (SSSs). A phenomenological approach was used in this qualitative research in which six males, two females, and eight SSSs participated. It has been seen that as a result of face-to-face interviews with participants within the framework of the semi-structured interview protocol, the spiritual support service has been experienced as a process which changes the perception of life. In participants' experience, spiritual support has a deeper and more positive impact than other psychosocial services. Research findings show the need for a more dynamic education process based on psychology and social sciences to enhance effective communication and interviewing skills.
Keywords: Islamic pastoral care; Muslim spiritual care givers; spiritual care in hospital; Turkey; CHAPLAINS; HEALTH; CARE